Highly efficient and robust aerobic co-oxidation of olefins and aldehydes over CoOx dispersed within hierarchical silicalite-1 zeolites - Li, Chenhao; Pu, Ning; Huang, Kaimeng; Xia, Changjiu; Peng, Xinxin; Lin, Min; Zhu, Bin; Xingtian Shu (Green chemistry : an international journal and green chemistry resource : GC, 2022)
Epoxide compounds are ultra-important intermediates for manufacturing a variety of chemical products, yet their industrial preparation still suffers from some non-negligible drawbacks. Herein, novel CoOx nanoparticles dispersed within internal channels of hierarchical silicalite-1 zeolite (CoOx/h-S-1) catalysts, for precisely controllable initiation and transfer of free radical oxygen species under mild conditions, were initially prepared via combining silane pore-expansion and metal chelation by N-containing ligands under hydrothermal crystallization conditions. By using multiple characterization methods, it has been confirmed that CoOx nanoparticles loaded within zeolite internal channels through Co–O–Si bonds are majorly with the chemical valence state of +2 and a tetrahedral coordination environment, especially low Co loading, favors a small CoOx nanoparticle size and a high Co–O–Si proportion. CoOx/h-S-1 shows promising catalytic activity and lifetime in aerobic co-oxidation of olefin and aldehyde with a broad substrate scope and with high selectivities of epoxide and carboxylic acid, respectively. Remarkably, it has been found that loaded CoOx nanoparticles play key roles in enhancing radical initiation and transformation and oxygen transfer of reactive oxygen species (ROS); thus the catalytic performance can be tuned by altering the properties of both the catalyst and substrates. Importantly, these radical processes are profoundly verified by the impact of catalyst properties on the cis–trans isomerism of epoxidized methyl oleate (EMO), radical inhibition experiments and radical trapping experiments with EPR spectroscopy analysis. Consequently, this work not only provides an efficient and green epoxidation route over robust catalysts with easily available O2 as the oxidant, but also systematically reveals the fundamental understanding of the rational design and construction of metal nanoparticles within hierarchical zeolite channels and the corresponding structure–activity relationship for ROS transformation, which benefits the further development of both the catalyst and process technology.